Особенности отношений к другим людям жителей городов юга России, дифференцированных по территориально-пространственно-временным параметрам проживания в городе - Шкурко, Татьяна Алексеевна; Балакина, Анна Андреевна (Rossijskij psihologičeskij žurnal., 2015)
In the article the spatial-temporal factors that influence the formation of attitudes towards other people, identified by their differential impact on the severity of the socio-psychological needs, settings, and types of relationships to other people the inhabitants of the metropolis, large and small cities. Determinants of the peculiarities of the relations to others are considered in the study: place of birth (city/town); areaof residence (center/periphery); type of residence (house, cottage/apartment building); height (floor) residence; duration of residence in the city; the presence and number of moving from one place to another; the type of move (within the same area/thesame region/ to other regions/to other country); the aim of moving. The respondents of empirical study were the inhabitants of the small (Krymsk) and large (Rostov-on-Don) cities of the South of Russia, as well as residents of the metropolis (Moscow). It is shown that the influence of spatial and temporal factors on the system of relationsto other people of a resident of the city is mediated by the type of city. The biggest influence had such factors as: “place of birth”, “type of residence”, “presence/absence of moving from one place to another, type of move”, “duration of residence”. The work demonstrates that spatial-temporal factors determine, primarily, the relationship toother people of residents of the metropolis and large towns, and, to a lesser extent, affect the relationship to others of the inhabitants of the small city.The results and conclusions of the study can be used in analysis, explanation, prediction of social phenomena (the protest movement, participation in rallies, migration) at the level of cities of various types (in the organization of events and actions in an urban environment; planning and implementation of elections campaigns for different target groups. В статье систематизированы территориально-пространственно-временные факторы, влияющие на формирование отношений к другим людям, определено их дифференцированное влияние на выраженность социально-психологических потребностей, параметров и типов  отношений к другим людям жителей мегаполиса, большого и малого городов. В качестве детерминант особенностей отношений к другим людям в исследовании рассматриваются: место рождения (город проживания/другой город); район проживания (центр/периферия); тип проживания (частный дом, коттедж/ многоквартирный дом); высота (этаж) проживания; длительность проживания в городе; наличие иколичество переездов; тип переезда (своя область/свой регион/другой регион/другая страна); цель переезда. Эмпирическим объектом исследования выступили жители малого (Крымск) и большого (Ростов-на-Дону) городов Юга России, а также жители мегаполиса (Москва). В работе показано, что влияние территориально-пространственно-временных факторов на систему отношений к другим людям жителя города опосредовано типом города. Наибольшее влияние оказывают такие факторы, как: «место рождения», «тип проживания», «наличие/отсутствие переезда», «тип переезда», «длительность проживания». В работе продемонстрировано, что территориально-пространственно-временные  факторы  обусловливают в первую очередь отношения к другим людям жителей мегаполиса и большого города, и в меньшей степени влияют на отношения к другим людям жителей малого города. Результаты и выводы исследования могут быть использованы при анализе, объяснении, прогнозировании общественных явлений на уровне городов различного типа (протестное движение, участие в митингах, миграция населения); при организации мероприятий и акций в городской среде; при планировании и реализации предвыборных кампаний для разных целевых групп.